Can We Educate and Train Aboriginal Leaders with our Tertiary Education Systems?. Issue 1 (22nd July 2010) - Foley, Dennis
Abstract: The concept of Aboriginal leadership often results in debate. The fundamental question raised is if Australian Aboriginal people are equal members of a pluralistic society that is based on co-operation and consensuses then how can you have a leader? Consequently who determines leadership or is a leader someone that in effect is more equal than others? Is leadership an attribute gained from within Aboriginal society or is leadership as we currently define it taught within the education structures of settler society? This paper briefly examines leadership from a postcolonial contemporary Aboriginal position, reviewing existing leadership education programs.